Analisis Pengaruh Umur Bangunan Terhadap Tingkat Kepuasan Penghuni: Analysis of the Effect of Building Age on Occupant Satisfaction Levels - Ramadhan, Muhammad Aulia Nur; Nugroho, Arief Setiawan Budi; Irawati, Inggar Septhia (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2023)
The relationship between residence and well-being, including physical health and emotional state, is widely recognized. Residence quality significantly impacts resident satisfaction, especially for students who require a conducive environment for effective learning. This study examines the impact of building age on resident satisfaction and willingness to pay at the Gadjah Mada University (UGM) dormitory. A questionnaire comprising 20 closed-ended questions evaluates building quality, management, and tariffs, while four questions gauge willingness to pay. With 136 responses from Dorm-50 (over 50 years old), Dorm-15 (over 15 years old), and Dorm-5 (under 5 years old), data is analyzed descriptively through multivariate analysis of variance and price sensitivity meter. Findings show that newer buildings do not always yield higher resident satisfaction. The socioeconomic background of the residents plays a crucial role in assessing satisfaction levels. MANOVA reveals distinct satisfaction levels among the three age groups concerning building quality, services, and rates. Price sensitivity assessment exposes disparities between current rentals and acceptable price ranges for occupants in each dorm. Certain floors or room types exceed acceptable rental ranges.